Molecular docking of selected flavonoid compounds from nelumbo nucifera as potential pancreatic lipase inhibitor - Ghazali, Siti Nur Akmal; Alias, Norsyuhada; Abdul Hamid, Azzmer Azzar (2017)
Obesity has been classified as a disease that affects many people around the globe including Malaysia. The prevalence continues to rise each year, thus finding an effective and safe treatment as an anti-obesity drug is a major issue to researchers. At present, the only anti-obesity that gained approval by the Food and Drug Administration (FDA) is Orlistat. It acts by inhibiting pancreatic lipase activity. Unfortunately it is a synthetic drug and comes with unpleasant side-effects. Hence, there is a need to search for pancreatic lipase inhibitor from natural resources. Several studies have revealed that flavonoids from Nelumbo nucifera leaves extract showed pancreatic lipase-inhibitory activity. In this study flavonoids from N. nucifera namely leucoanthocyadin, rutin and astragalin were chosen to undergo molecular docking analysis using AutoDock 4.2. Molecular docking is an in silico method to predict the binding site of the selected compounds towards pancreatic lipase structure. Docking simulation revealed that astragalin displayed the best affinity towards pancreatic lipase as compared to the other two flavonoids. Astragalin produced more hydrogen bonds and had lower free binding energy compared to orlistat. Moreover, astragalin formed strong hydrogen bond with key amino acid Ser 152 in the catalytic triad and showed good ligand recognition as it also had strong hydrogen bond with His 151, Phe 215 and Arg 256. This preliminary in silico result proposes that astragalin might act as an anti-obesity agent through pancreatic lipase inhibition action.